Gender violence and social networks in adolescents. The case of the province of Malaga. - Mena-Rodríguez, Esther; Velasco-Martínez, Leticia Concepción (My University, 2017)
Gender violence and the violence exerted on social networks are particularly current issues of interest for both the scientific community and the media. When both types of violence are present during adolescence, a more specific area of study arises that is circumscribed to cyberbullying exerted and suffered by adolescents on the Internet. This work is part of a larger project carried out in secondary schools in Spain, with special focus on Andalusia (financed by BBVA, 2014-2016). The case here presented is the one for the province of Malaga. The educational community of Malaga is of a peculiar and heterogeneous nature that combines a large foreign section of the population that was the result of tourism (since the seventies in the past century) with other migratory phenomena that are shared with other regions of Spain. The purpose of the study was to show the prevalence of gender violence among adolescent students in the 15-17-year age bracket from the province of Malaga, and to identify the predictive factors of occasional and frequent violence on social networks. A survey was designed and validated that was applied in electronic format to a random sample of public schools in Malaga (n=282). The sample size allowed us to work with an error of ±0.06 (confidence level of 95%). The results and conclusions identify predictive factors of occasional and frequent violence, and suggest improvements to be made in action guidelines and protocols, as well as in the action to foster awareness among adolescents and the general public in regard to these issues
Keywords: Adolescentes - Psicología; Violencia de género; Acoso moral en la escuela; Ciberacoso; Student violence; Bullying; Cyberbullying; Adolescents